2014
DOI: 10.4172/2157-7110.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heating and of Short Exposure to Sunlight on Carotenoids Content of Crude Palm Oil

Abstract: This study was done to evaluate the effect of short exposure to sunlight and of heating on crude palm oil (CPO) quality particularly on its carotenoids content. Firstly, CPO was exposed to sunlight for 14 hrs. Then, samples were collected and kept at 4°C for analysis of carotenoids content, free fatty acid (FFA) and peroxide value (PV). Secondly, CPO was heated at 50°C, 120°C, 200°C or 400°C for 30 min, 60 min or 120 min and samples were cooled down and kept at 4°C until analysis of carotenoids content, FFA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
4
4
0
Order By: Relevance
“…The outcome postulated that major contribution of the degradation of carotenoid in PPMO is temperature instead of light at temperature not more than 35°C. The finding is in good agreement with Fabrice, reported that significant carotenoid degradation caused by temperature applied to crude palm oil (Fabrice Fabien et al, 2014). Schroeder and Johnson (1995) also reported that carotenoids are vulnerable to enzymatic or nonenzymatic oxidation where rate and extent of oxidation depend on the structure of carotenoid, the presence of prooxidants and antioxidants, high temperature, light exposure, oxygen availability, enzyme types and metals.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The outcome postulated that major contribution of the degradation of carotenoid in PPMO is temperature instead of light at temperature not more than 35°C. The finding is in good agreement with Fabrice, reported that significant carotenoid degradation caused by temperature applied to crude palm oil (Fabrice Fabien et al, 2014). Schroeder and Johnson (1995) also reported that carotenoids are vulnerable to enzymatic or nonenzymatic oxidation where rate and extent of oxidation depend on the structure of carotenoid, the presence of prooxidants and antioxidants, high temperature, light exposure, oxygen availability, enzyme types and metals.…”
Section: Resultssupporting
confidence: 92%
“…Both typical and optimum-case conditions exhibited similar retention percentage, approximately 82% and similar t 1/2 whereas worst-case condition showed significantly low retention percentage and t 1/2 (Tables 2 and 3 and Supplementary Table 2). The outcome postulated that major contribution of the degradation of carotenoid in PPMO is temperature instead of light at temperature not more than 35 C. The finding is in good agreement with Fabrice, reported that significant carotenoid degradation caused by temperature applied to crude palm oil (Fabrice Fabien et al, 2014). Schroeder and Johnson (1995) also n.d. 0.1 ± 0.0 0.1 ± 0.1 0.1 ± 0.0 0.1 ± 0.1 C16:0 33.3 ± 2.0 34.8 ± 0.8 34.2 ± 0.4 36.0 ± 1.1* 39.9 ± 0.4 41.7 ± 0.1* 41.2 ± 0.8 43.0 ± 1.7* 15.8 ± 1.3 15.1 ± 0.4 14.3 ± 0.6 16.9 ± 1.0 7.8 ± 0.5 7.8 ± 0.2 6.6 ± 0.4 8.7 ± 1.3 C16:1 0.4 ± 0.0 0.4 ± 0.0 0.5 ± 0.2 0.4 ± 0.1 0.3 ± 0.1 0.5 ± 0.0 0.4 ± 0.0 0.5 ± 0.1 1.4 ± 0.0 1.3 ± 0.0 1.3 ± 0.1 1.4 ± 0.1 0.2 ± 0.2 0.9 ± 0.1 0.1 ± 0.0 1.5 ± 0.1 C18:0 3.6 ± 0.3 3.4 ± 0.2 3.4 ± 0.1 3.1 ± 0.4 4.2 ± 0.1 4.1 ± 0.0 4.3 ± 0.1 3.9 ± 0.3 n.d.…”
Section: Resultssupporting
confidence: 82%
“…This is due to the high viscosity, high melting points, and the high levels of SFA present in TO, owing to which these oils solidify readily under ambient conditions within a short time. Marketers or vendors address this challenge by exposing the oils to sunlight to liquefy the solidified oils and maintain the liquid or semi‐solid forms (Ngono Ngane Annie, 2014), which increases marketability and consumer acceptance. While these practices are suitable from the marketing and economics outlook, from a scientific perspective, they pose risks to the stability of the oils by oxidation or related decomposition and are inappropriate (Maszewska et al, 2018; Oh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the high viscosity, high melting points, and the saturated fatty acids present in TOs, owing to which, these oils solidify readily under ambient conditions within a short time. Marketers or vendors address this challenge by exposing the oils to sunlight for liquefying the solidified oils and maintaining the liquid or semi-solid forms (Ngono Ngane Annie, 2014), which increases the marketability and consumer acceptance. While these practices are suitable from the marketing and economics outlook, from a scientific perspective, they pose risks to the stability of the oils by oxidation or the related decomposition and are inappropriate (Maszewska et al, 2018& Oh et al, 2014.…”
Section: Introductionmentioning
confidence: 99%